Teaching Practices of a Warehousing Management Curriculum based on Virtual Reality Simulation Technology - He, Dan (International Journal of Emerging Technologies in Learning (iJET), 2022)
Warehousing management is a specialized core curriculum in the logistics management major. The curriculum not only teaches strong theoretical concepts, but also practical skills. Traditional teaching mode emphasizes on theoretical teaching due to the lack of sufficient practical conditions; hence, students’ practical abilities cannot be developed comprehensively. Therefore, this study proposed teaching reform measures, such as reconstructing the curriculum content, implementing modularized teaching, and creating a build-task-exercise-evaluation teaching mode by introducing virtual reality (VR) simulation technology and improving the teaching method. With these measures, students could finish their tasks and realize their learning objectives in the virtual intelligent warehouse environment by combining the knowledge and skills they have learned. Moreover, students were asked to design a warehouse layout by using the simulation software according to enterprise case data. Results show that the task-driven teaching reform for warehousing management curriculum based on VR technology improves the efficiency and quality of students’ skill training.